An exploration of male and female managers' perspectives on the meaning and assessment of commitment: Cases from leading British and Swedish engineering companies - Singh, Val (Cranfield University, 1999)
This thesis explores the issue of why female managers’ commitment is so often reported as being less of that of males, despite research evidence that there is no gender difference in levels of commitment. No previous research was found which reported managerial meanings of “commitment”, usually conceptualised with an affective component resulting in loyalty and effort, and a continuance component, the desire to stay in an organisation. Meanings of “commitment” in three major engineering companies were elicited through interviews with 37 engineering managers in the UK and Sweden. The sample included sixteen male/female pairs matched on age, qualifications and job position, from top, middle and junior levels of management. The meanings important to managers were the manifested behaviours of commitment at work. The most common of the 36 elicited meanings were task delivery, putting yourself out, involvement, and quality. Overall, male meanings were more similar to top managers’ meanings than female meanings. Top women’s meanings were similar to those of top men, sharing meanings of being proactive/using initiative, being ready for challenge, being creative/innovative, and being business aware. More women overall gave meanings oriented towards the organisation, particularly good citizen behaviours, which would be less visible to managers, whilst more men overall gave meanings, benefiting themselves as well as the organisation, which were very active and highly visible. Five types of commitment meanings were identified: Virtuous, Volunteer, Virtuoso, Vanguard and Gender-Shared. In a later questionnaire, the sample were asked to rate the importance of their 36 meanings of commitment in terms of their own view and their perceived view of how their organisation would rate them. Through gaps between individual and perceived organisational ratings, tensions were identified and mapped, providing a guide for an indepth analysis of meanings with the greatest tensions, particularly on hours over the norm perceived to be valued more by the organisation, and on getting balance, enjoying work, thinking of oneself as well as the organisation, and being people-concerned. Interviewees at all levels indicated the importance of getting work/nonwork balance, most rejecting the notion of commitment meaning working additional hours. Attitudes to managers seeking maternity/paternity leave were reported. Through the Swedish comparison, a trend was identified that where most male managers take extended paternity leave, the issue which is seen as a woman’s individual problem in the UK becomes an organisational planning issue in Sweden. Thus, perceived lesser commitment is transformed into less unplanned availability for a short period. The process of commitment assessment has also been explored and a number of dimensions drawn out, particularly the tacit nature of the evidence, the subjectivity of assessment, and the manager’s susceptibility to influence. These affect the way in which commitment behaviours are interpreted by the manager, as both males and females use impression management strategies to demonstrate their commitment. The contribution of this thesis is to the commitment field, in identifying managers’ meanings of commitment, and to the women in management field, where evidence is presented of the differences in male and female meanings of commitment, and the importance of visibility of commitment to managers. As women’s meanings are less visible than those of men in this sample, this suggests an explanation of why women’s commitment is still challenged.